234k views
3 votes
Please Help it’s Urgent

Please Help it’s Urgent-example-1
User Hon
by
5.2k points

1 Answer

6 votes

Answer:

x = 6

Explanation:

Let's solve for x in the following equation:

√(2x - 3) + 3 = x

√(2x - 3) = x - 3 (Subtracting 3 at both sides)

(√(2x - 3))² = (x - 3)² (Raising at the second power at both sides)

2x - 3 = x² -6x + 9

0 = x² - 8x + 12 (Building quadratic equation)

0 = (x - 6) (x -2) (Factoring)

x₁ = 6

x₂ = 2

Proof of x = 6

√(2x - 3) + 3 = x

√(2 * 6 - 3) + 3 = 6

√(12 - 3) + 3 = 6

√9 + 3 = 6

3 + 3 = 6 ⇒ We proved that x = 6 is correct

Proof of x = 2

√(2x - 3) + 3 = x

√(2 * 2 - 3) + 3 = 2

√(4 - 3) + 3 = 2

√1 + 3 = 2

1 + 3 ≠ 6 ⇒ We proved that x = 2 is incorrect

User RaduM
by
5.0k points